The teaching of development economics : its position in the present state of knowledge :proceedings - Martin, Kurt; Knapp, John.; Victoria University of Manchester (London : Frank Cass, 1967)
This is an eight articles volume that examines the teaching of development economics. The book also discussed weaknesses and strengths of economic analysis, as well as approaches to teaching development economic.
Conference held under the auspices of the Centre of Development Studies, University of Manchester.
Includes index
Includes bibliographical footnotes.
lje 24/01/2018
Loans
Keywords: Economic development; Development economics; Developing countries